A Low-Cost Remote Healthcare Monitor System Based on Embedded Server - He Liu; Yadong Wang; Lei Wang (Institute of Advanced Engineering and Science, 2013)
In the paper, we propose a scheme about a low-cost remote healthcare monitor system based on embedded server between home and hospital. In the scheme, we design an embedded server based on an ARM9 microprocessor. The embedded server supplies all kinds of interfaces such as GPIO interfaces, serial interfaces. These interfaces can acquire all kinds of physiology signals such as Electrocardiograph, heart rate, respiration wave, blood pressure, oxygen saturation, body temperature and so on through connecting the sensor modules. The network is based on local area network and adopts the Browser/Server model. Each home with an embedded server is as a server endpoint and the hospital is as a Browser endpoint. Every embedded server owns an independent static internet protocol address. The doctors can easily acquire patients’ physiology information through writing patients’ internet protocol address on any computer browser. The embedded server can store patients’ physiology information using database in an 8 GB SD card. The doctor can download the database information into the local computers. The system can conveniently upgrade all software in the embedded server only on a remote hospital computer. The remote healthcare monitor system based on embedded server has advantages of low-cost, convenience and feasibility. DOI: http://dx.doi.org/10.11591/telkomnika.v11i4.2327